Circle of Willis Variants and Their Association with Outcome after Successful Revascularization of Anterior Large Vessel Occlusion - Sriwastwa, Aakanksha; Oswald, Michael K.; Vagal, Achala S.; Demel, Stacie L.; Zhang, Bin; Voleti, Sriharsha; Ali, Arafat; Morgan, Daniel; Thompson, Trevor; Vidovich, Johnathan; Aziz, Yasmin N.; Wang, Lily Li-Li (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: Leptomeningeal collaterals have been associated with better outcomes in large-vessel stroke, but little is known about how the circle of Willis (CoW) collaterals affect stroke outcomes. We aimed to determine the relationship between 3 anatomically distinct CoW subtypes and 90-day outcomes in patients with acute ischemic stroke after successful revascularization via endovascular thrombectomy (EVT).MATERIALS AND METHODS: We performed a retrospective analysis of patients treated with successful EVT for large-vessel occlusion at a comprehensive stroke center between May 2016 and November 2023. The CoW anatomy was trichotomized by using baseline CT angiography as follows: 1) complete circle of Willis (C-CoW), 2) nonisolating incomplete circle of Willis (NI-CoW), and 3) isolating incomplete circle of Willis (I-CoW). χ2 and logistic regression analyses were utilized to determine the association of the CoW subtype with 2 coprimary outcomes: the 90-day mRS and 90-day mortality.RESULTS: A total of 465 patients were included in the analysis. Multivariable logistic regression analysis demonstrated a significant association between I-CoW and 90-day mRS compared with NI-CoW (OR [95% CI], 1.83 [1.08–3.09]; P = .02). Additionally, I-CoW anatomy was associated with a higher 90-day mortality than C-CoW (OR [95% CI], 2.58 [1.01–6.60]; P = .04) and NI-CoW (OR [95% CI], 1.89 [1.13–3.18]; P = .01).CONCLUSIONS: CoW variants are associated with functional and mortality outcomes in patients treated with EVT for anterior circulation large vessel occlusion. Further research is needed to determine how CoW vessel anatomy may impact clinical assessment, triage, and treatment in acute ischemic stroke.ACAanterior cerebral arteryAComanterior communicating arteryAISacute ischemic strokeCoWcircle of WillisC-CoWcomplete circle of WillisEVTendovascular thrombectomyI-CoWisolating incomplete circle of WillisLVOlarge vessel occlusionmTICImodified treatment in cerebral infarctionNI-CoWnonisolating incomplete circle of WillisPCAposterior cerebral arteryPComposterior communicating arteryTan CSTan collateral scores